Socialization and Production of Ecoenzyme Fluid in Tanjung Kasau Plantation Village, Batubara District - Siringoringo, Yan Batara Putra; Marpaung, TJ; Syahputra, Razak Kurnia; Napitupulu, Normalina; Zahedi (Talenta Publisher, 2023)
Ecoenzyme is a solution of complex organic substances produced by the fermentation process of organic waste, water, and molasses. So that organic waste that has been disposed of and is no longer used can be utilized as an environmentally friendly product. This eco-enzyme solution is dark brown in color and has a strong sour aroma. This socialization and demonstration focuses on making Ecoenzyme solutions from organic waste grapefruit, pumpkin, kale, chicory and papaya from household waste which aims to educate the public, especially housewives in Tanjung Kasau Plantation Village to know the procedure for making Ecoenzyme and using waste organic. Using an experimental method, an Ecoenzyme solution was made with 1 part molasses, 3 parts fruits and vegetables, and 10 parts clean water and then fermented for 3 months to make an Ecoenzyme solution. For the first 1 month the test was carried out Periodically, samples are taken every 2 days and evaluated for find out the evaluation parameters including organoleptic, pH and appropriate viscosity established test procedures. The results of this study showed that a good Ecoenzyme had a dark brown color, a fresh sour aroma typical of spicy and get a stable pH with a pH of 4.0 showing a high eco-enzyme produced is acidic which has benefits such as radiation protection, clearing drains, floor cleaners, organic disinfectants etc.